2020
DOI: 10.3390/s20174788
|View full text |Cite
|
Sign up to set email alerts
|

Arousal Detection in Elderly People from Electrodermal Activity Using Musical Stimuli

Abstract: The detection of emotions is fundamental in many areas related to health and well-being. This paper presents the identification of the level of arousal in older people by monitoring their electrodermal activity (EDA) through a commercial device. The objective was to recognize arousal changes to create future therapies that help them to improve their mood, contributing to reduce possible situations of depression and anxiety. To this end, some elderly people in the region of Murcia were exposed to listening to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Valence refers to pleasantness, i.e., the degree of positive or negative affect, whereas arousal refers to the energetic component of the emotion (alertness). Research has consistently linked skin conductance to arousal (Christopoulos et al, 2019;Bartolomé-Tomás et al, 2020). Also, other types of physiological responses have been found to generally map better on arousal rather than valence (Mauss and Robinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Valence refers to pleasantness, i.e., the degree of positive or negative affect, whereas arousal refers to the energetic component of the emotion (alertness). Research has consistently linked skin conductance to arousal (Christopoulos et al, 2019;Bartolomé-Tomás et al, 2020). Also, other types of physiological responses have been found to generally map better on arousal rather than valence (Mauss and Robinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As the field of machine learning has evolved over the last decade, these algorithms have been used to train models for predicting various outcomes based on EDA data or multi-sensor data including EDA. Examples from works published within the last few years include classification of epileptic seizures (Zsom A and et al, 2019), differentiation of sensory responses for children with autism spectrum disorder (Raya MA et al, 2020), identification of cognitive tasks (Posada-Quintero HF and Bolkhovsky JB, 2019), pain assessment (Susam BT et al, 2018;Posada-Quintero HF et al, 2021;Aqajari SAH et al, 2021), emotion recognition (Al Machot F et al, 2019;Sharma V et al, 2019;Ganapathy N et al, 2020), assessment of emotional engagement (Di Lascio E et al, 2018), Stress detection (Amalan S and et al, 2018;Zontone P et al, 2019;Pakarinen T et al, 2019;Anusha AS et al, 2020;Sánchez-Reolid R et al, 2020;Greco A and et al, 2021), cognitive load measurement (Romine WL et al, 2020), detection of major depressive disorder (Kim AY et al, 2018), and arousal detection from music ( Bartolomé-Tomás A et al, 2020). Among these studies, high performances in classification accuracies have been reported ranging from 64% to 95% depending on the dataset, classification problem and difficulty A c c e p t e d M a n u s c r i p t (binary classification is for instance less challenging than multiple levels of stress).…”
Section: Machine Learningmentioning
confidence: 99%
“…We believe that higher quality data, collected in an in-person setting, might give additional insights into the combination of individual features. Additionally, the use of physiological measures, such as Electroencephalography (EEG) or Electrodermal activity (EDA) as objective markers of engagement during music listening has recently revealed promising results [29,30,31]. Future studies should address the overlap between subjective tension ratings and objective neural data.…”
Section: Limitationsmentioning
confidence: 99%